(untitled) (Prilozi za orijentalnu filologiju, 2017)
In the international politics arena the Ottoman Empire was rather pragmatic and very often considered Islamic law to be of secondary significance, turning to objective possibilities and interests instead. It is evident that the Porte in international relations manipulated with a certain spectrum of political mechanisms, far from the Islamic legal code and yet very much a part of real-politik (military force, political-diplomatic activities or pressures of material or fiscal character). The Ottoman administration never had a consistent politics in issuing capitulations. Capitulations were issued to foreign sovereign countries as compensation for political collaboration, alliance or peace. Practice has also shown that tribute-paying countries received capitulations in cases when, from the Porte’s perspective, it was opportune to support a political project, a group or program in a particular tributary country. Ottoman capitulations should, for that reason, be considered as political instruments. Even though Islamic theory on international relations anticipated the capitulations as political instruments, as well as there was always a tendency toward keeping them within the frame of Islamic law, issuing the capitulations was not an ideologically, but politically and pragmatically motivated case. Therefore, in the aim of defining the relations and obligations in relationship towards “the other side” the Porte used terminology which stemmed from Islamic Law. However that relationship never needed to be strictly consistent with Islamic law. Even though the main idea of the Dubrovnik’s capitulation was mostly drawn up according to the rules of Islamic law, partially it does consist of certain elements that surpass the theoretical concept of relations toward tribute-paying countries. From a legal perspective which emanate from the theory of asymmetrical relationships in Islamic law, as long as Dubrovnik paid its haraç it was subject to the Porte’s military and political protection. The haraç, of course, wasn’t the only obligation. Dubrovnik was expected to adapt its domestic and foreign politics to the Porte’s politics. However, Dubrovnik’s haraç was symbolic, since it didn’t really amount to much for the Porte, it seems that Dubrovnik’s political role was much more significant to the Porte than haraç. Therefore, if we are to sublime the status of the Republic of Dubrovnik within the context of the above-mentioned interpretations, we could conclude that principally Dubrovnik belonged to darü’l-’ahd. However, it is obvious from the capitulations that the Republic of Dubrovnik retained the high degree of political integrity which, contrary to expectations and the Islamic law, sometimes resembled the elements of independence, all in the conformity with the Porte’s pragmatic interests.